A INFOGRAFIA MULTIMÍDIA NO CLARÍN.COM E FOLHA.COM: o Flash e o HTML5 na ampliação das características interativas - Barboza, Eduardo Fernando Uliana (2015)
This paper aims a comparative study of the use of multimedia infographics by the sites Clarín.com, from Argentina and Folha.com, from Brazil. The research aims to determine and analyze how these two important online media in Latin America have used new technologies like HTML5 to modernize the information that they present. Therefore, the comparative analysis will stick to the multimedia infographics, which has undergone profound technological changes, changing the format and the content of the news. Besides the theoretical conceptualization and review of literature on infographics, newsgame, transmedia storytelling, online journalism, interactivity and programming languages used to produce multimedia infographics, the paper will bring foward a comparative analysis of the section Infografia, presented by Folha.com, and Especiales Multimedia, by Clarín.com. The analysis, quantitative and qualitative, will check the narrative and informational resources, tools and Internet programming language technologies that are used by the two media, based on the analysis model proposed by Alberto Cairo in the book Infografia 2.0 visualización interactiva de información en prensa. The research has shown that although the Clarín.com has used Flash technology in most multimedia infographics analyzed, the results of comparative analysis show that the Argentine online newspaper infographics allowed higher levels of interactivity than multimedia infographics in Folha.com, mostly developed in HTML5.